Pemodelan Sistem Rekomendasi Pemilihan Paket Internet IndiHome Menggunakan Metode Knowledge - Lestari, Fany; Hartanti, Dwi; Hasanah, Herliyani (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
As time goes by, the internet has become a basic human need. There are various internet service providers with various and interesting products. Each internet service provider has its own advantages and disadvantages. This makes customers confused about choosing a suitable internet package to use to support their activities. The Indihome internet package selection recommendation system uses a knowledge-based method and is designed to help users choose an internet package that suits their needs. This knowledge based method is based on existing knowledge. The use of a knowledge base is easy for users to understand and makes it possible to produce recommendations that suit user needs. It is hoped that the results of this system can be used as a consideration for consumers in making decisions regarding selecting the internet service package to be used and increasing customer satisfaction.